Recruitment of endogenous progenitor cells by erythropoietin loaded particles for in situ cartilage regeneration - Amirhossein Hakamivala (Bioactive Materials, 2020)
Cartilage injury affects millions of people throughout the world, and at this time there is no cure. While transplantation of stem cells has shown some success in the treatment of injured cartilage, such treatment is limited by limited cell sources and safety concerns. To overcome these drawbacks, a microscaffolds system was developed capable of targeting, reducing the inflammatory response and recruiting endogenous progenitor cells to cartilage-defect. Erythropoietin (EPO)-loaded-hyaluronic acid (HA) microscaffolds (HA + EPO) were fabricated and characterized. HA-microscaffolds showed good cell-compatibility and could target chondrocytes via CD44 receptors. HA + EPO was designed to slowly release EPO while recruiting progenitor cells. Finally, the ability of HA + EPO to repair cartilage-defects was assessed using a rabbit model of full-thickness cartilage-defect. Our results showed that the intra-articular administration of EPO, HA, and EPO + HA reduced the number of inflammatory cells inside the synovial-fluid, while EPO + HA had the greatest anti-inflammatory effects. Furthermore, among all groups, EPO + HA achieved the greatest progenitor cell recruitment and subsequent chondrogenesis. The results of this work support that, by targeting and localizing the release of growth-factors, HA + EPO can reduce inflammatory responses and promote progenitor cells responses. This new platform represents an alternative treatment to stem-cell transplantation for the treatment of cartilage injury. Keywords: Hyaluronic acid microscaffolds, Erythropoietin, Progenitor cells recruitment, Chondrogenesis, Cartilage injury